2022
DOI: 10.20884/1.jks.2022.17.1.5297
|View full text |Cite
|
Sign up to set email alerts
|

Remote Learning for Nursing Education in Indonesia during The Covid-19 Pandemic: Efforts and Recommendations

Abstract: The COVID-19 pandemic had an impact on nursing students’ academic and clinical performance. Nursing institutions have provided remote learning to continue the learning process. However, students have met several obstacles that caused a decrease in the quality of learning. Remote learning for education requires the support of information and communication technology. However, studies related to how the COVID-19 pandemic affected nursing education in Indonesia are still rarely done. Accordingly, this study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Hunter & Arthur's (2016) research findings, the virtual case learning system motivated and stimulated students to improve their clinical reasoning. A study in Indonesia found that during the COVID-19 pandemic, most of the teaching materials were provided through visual delivery methods (24%), text (21%), and audiovisuals (20%) (Haryanti et al, 2022). An efficiency study that compared the BL method with conventional methods in nursing education also proved that 68% of students preferred the BL model and that it contributed to the increase in the students' scores (Shang & Liu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hunter & Arthur's (2016) research findings, the virtual case learning system motivated and stimulated students to improve their clinical reasoning. A study in Indonesia found that during the COVID-19 pandemic, most of the teaching materials were provided through visual delivery methods (24%), text (21%), and audiovisuals (20%) (Haryanti et al, 2022). An efficiency study that compared the BL method with conventional methods in nursing education also proved that 68% of students preferred the BL model and that it contributed to the increase in the students' scores (Shang & Liu, 2018).…”
Section: Discussionmentioning
confidence: 99%